Composite positive electrode material for lithium-sulfur battery and preparation method of composite positive electrode material

By using sulfurized cobalt -containing cobalt -containing cobalt compound nitrogen -doped graphene as a sulfur positive vector in lithium sulfur batteries, the problem of serious lithium shuttle shuttle effects in lithium sulfur batteries has been solved, and high -efficiency catalytic conversion and stable cycle is achieved. The capacity and stability of the battery.

CN119381427APending Publication Date: 2025-01-28HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411415756.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Lithium-sulfur batteries face problems such as electronic insulation of sulfur element, serious shuttle effect of intermediate product lithium polysulfide, obvious volume effects of sulfur and discharge end products, resulting in low utilization rate of sulfur cathode, serious capacity attenuation, and shortened cycle life.

Method used

The sulfide composite nitrogen doped graphene with a sulfur -containing deficiency is used as a sulfur orthopedic pole carrier, and the composite positive pole material for lithium sulfur batteries is formed through the thermal treatment method to compound the sulfur monochrome to improve the compulsory adsorption of lithium sulfide. Efficient catalytic conversion ability.

Benefits of technology

Effectively inhibit the shuttle effect of lithium sulfide, stabilize the battery cycle, and obtain a high -capacity and high stability lithium sulfur battery composite positive pole material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381427A_ABST
    Figure CN119381427A_ABST
Patent Text Reader

Abstract

The invention discloses a composite positive electrode material for a lithium-sulfur battery and a preparation method of the composite positive electrode material. The composite positive electrode material is obtained by compounding cobalt sulfide composite nitrogen-doped graphene containing sulfur defects and elemental sulfur, the preparation method comprises the following steps: preparing cobalt sulfide composite nitrogen-doped graphene containing sulfur defects by using a one-step sintering method, and then compounding the cobalt sulfide composite nitrogen-doped graphene with elemental sulfur by using a heat treatment method. The preparation method is mature in process and simple in process. According to the lithium-sulfur battery composite positive electrode material disclosed by the invention, the relatively good strong chemical adsorption and charge transfer effects of cobalt sulfide containing sulfur defects on lithium polysulfide are utilized, so that the shuttle effect of lithium polysulfide is greatly slowed down, the reaction kinetics is accelerated, and the lithium-sulfur battery composite positive electrode material has the characteristics of high sulfur content, high specific capacity and high cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a composite positive electrode material for a lithium-sulfur battery and a preparation method thereof. Background Art

[0002] With the growing demand for electric vehicles and mobile electronic products in countries around the world, there is an urgent need for secondary batteries with high energy density, long cycle life and low cost. Lithium-sulfur batteries are considered to be one of the most promising alternative batteries that can meet these needs. Their theoretical energy density can reach 2600 Wh / kg, which is much higher than the energy density of currently commercialized lithium-ion batteries. The positive electrode of lithium-sulfur batteries is generally sulfur, and sulfur is abundant in the world, low in price, and environmentally friendly, which makes sulfur more conducive to commercialization as a positive electrode material. However, lithium-sulfur batteries face a series of problems such as sulfur electronic insulation, severe shuttle effect of intermediate product lithium polysulfide, and obvious volume effect of sulfur and discharge end products, resulting in low utilization rate of sulfur positive electrode of lithium-sulfur batteries, severe capacity decay, and shortened cycle life. In the face of the high energy density requirements of commercial sulfur cathodes with high sulfur loading and less electrolyte, the above problems will be more prominent.

[0003] To solve these problems, many scholars have made many efforts. For example, various carbon-based materials are used as host carriers of sulfur cathodes to improve electrode conductivity and adsorb intermediate lithium polysulfide. Later, some transition metal compounds were studied successively, such as sulfides, nitrides, phosphides, carbides and borides as host materials for sulfur, among which the electrocatalytic conversion of lithium polysulfide by transition metal compounds can effectively improve the electrochemical performance. However, under the current circumstances, how to further improve the utilization rate of sulfur cathodes, therefore, the catalytic ability of sulfur carrier materials still needs to be adjusted and improved.

[0004] Recently, surface defect engineering of support materials, such as oxygen vacancies, sulfur vacancies, phosphorus vacancies, selenium vacancies and other anion vacancies, has provided a possible strategy to improve the catalytic conversion of lithium polysulfides in lithium-sulfur batteries. Summary of the invention

[0005] To solve the above problems, the present invention provides a composite positive electrode material for a lithium-sulfur battery and a preparation method thereof, which utilizes the strong chemical adsorption and efficient catalytic conversion of cobalt sulfide with sulfur defects on lithium polysulfide, reduces the dissolution and shuttling of lithium polysulfide in ether electrolytes, and effectively improves the cycle performance of the assembled lithium-sulfur battery.

[0006] The present invention is achieved through the following technical solutions: The present invention provides a method for preparing a composite positive electrode material for a lithium-sulfur battery. The method comprises: preparing sulfur-defective cobalt sulfide composite nitrogen-doped graphene as a sulfur positive electrode carrier by a one-step sintering method, and compounding the composite positive electrode material with sulfur element by a heat treatment method.

[0007] Further, the method specifically includes the following steps: Step 1: Grinding a cobalt source, a sulfur source, a polymer and nitrogen-doped graphene to obtain a uniform mixture precursor, calcining the mixture precursor under a specific atmosphere, and then grinding it again to obtain a product, namely, sulfur-defective cobalt sulfide composite nitrogen-doped graphene; Step 2: Grind the prepared sulfur-defective cobalt sulfide composite nitrogen-doped graphene and sulfur element continuously for 0.5 h, then place it into a reactor and heat-treat it to obtain a composite positive electrode material S / Co for lithium-sulfur batteries. 9 S 8-x / NG.

[0008] Furthermore, in step 1, the cobalt source is cobalt nitrate hexahydrate, and the sulfur source is thioacetamide.

[0009] Furthermore, in step 1, the polymer is polyethylene glycol with a molecular weight of 20,000.

[0010] Furthermore, in step 1, the specific method for preparing the mixture precursor is: firstly place the cobalt source, the sulfur source, and the polymer in a mortar and mix and grind for 9 to 10 minutes, and then add the nitrogen-doped graphene and continue grinding for 19 to 20 minutes.

[0011] Furthermore, in step 1, the specific conditions of calcination under the specific atmosphere are calcination at 900° C. for 2 h in a hydrogen / argon mixed atmosphere.

[0012] Furthermore, in step 2, the mass ratio of sulfur-defective cobalt sulfide composite nitrogen-doped graphene to sulfur element is 28:72.

[0013] Furthermore, in step 2, the specific conditions of the heat treatment method are: heating to 155°C at a rate of 2°C / min under an argon atmosphere and maintaining for 12 h.

[0014] The present invention also provides a composite positive electrode material for a lithium-sulfur battery prepared by the above preparation method.

[0015] The beneficial effects of the present invention are: (1) The present invention adopts a one-step sintering method to prepare a sulfur-defective cobalt sulfide composite nitrogen-doped graphene material, and the process is mature; and then a heat treatment method is used to composite it with sulfur element to obtain a composite positive electrode material, which is simple and easy to obtain a high sulfur content composite positive electrode material; (2) Cobalt sulfide has good thermodynamic stability and high electrical conductivity. After producing defects, cobalt sulfide has better strong chemical adsorption and catalytic conversion capabilities for polysulfides, which can effectively inhibit the shuttle effect and stabilize the battery cycle, thereby obtaining a lithium-sulfur battery composite positive electrode material with high capacity and high stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the XRD pattern of the cobalt sulfide composite nitrogen-doped graphene containing sulfur defects prepared in Example 1; Figure 2 The first week charge and discharge curve of the lithium-sulfur battery composite positive electrode material prepared in Examples 1 to 4 at room temperature and 0.1 C rate; Figure 3 The lithium-sulfur battery composite positive electrode materials prepared in Examples 1 to 4 exhibit different cycle stabilities at room temperature and 0.1 C rate. DETAILED DESCRIPTION

[0017] The principle adopted by the present invention is: When anion defect carriers regulate composite sulfur cathodes, they use the coordination unsaturated structure to regulate local electron redistribution, thereby enhancing the polar adsorption of polysulfides; and the edges of the defect structure can produce more catalytic active sites, improve the reaction dynamics of polysulfide redox, and achieve better charge and discharge characteristics of lithium-sulfur batteries. Therefore, when anion defect-based transition metal compounds are used as sulfur cathode carriers, due to the special microstructure regulation, the carrier is endowed with the characteristics of strong binding with lithium polysulfide and high catalytic activity for polysulfides, the catalytic performance and efficiency of the catalyst will be further improved, and a high-performance lithium-sulfur battery with stable cycle stability can be obtained.

[0018] The present invention provides a method for preparing a composite positive electrode material for a lithium-sulfur battery. The method comprises: preparing sulfur-defective cobalt sulfide composite nitrogen-doped graphene as a sulfur positive electrode carrier by a one-step sintering method, and compounding the composite positive electrode material with sulfur element by a heat treatment method.

[0019] The specific steps include: Step 1: Preparation of sulfur-defective cobalt sulfide composite nitrogen-doped graphene: 0.6 g of cobalt nitrate hexahydrate, 1.5 g of thioacetamide, and 0.15 g of polymer were mixed and ground in a mortar for 10 min, and then 0.1 g of nitrogen-doped graphene was added and ground for 20 min to obtain a uniform mixture precursor. The mixture precursor was placed in a corundum boat in a tube furnace and calcined at 900 ° C for 2 h in a 10% hydrogen / argon mixed atmosphere, and then ground again. The product was cobalt sulfide composite nitrogen-doped graphene containing sulfur defects; wherein the polymer was polyethylene glycol with a molecular weight of 20,000.

[0020] Step 2: Compounding the sulfur-defective cobalt sulfide composite nitrogen-doped graphene obtained in step 1 with sulfur: The prepared sulfur-defective cobalt sulfide composite nitrogen-doped graphene and sulfur element were ground continuously for 0.5 h at a mass ratio of 28:72, and then placed in a reactor for heat treatment to obtain a composite positive electrode material S / Co for lithium-sulfur batteries.9 S 8-x / NG. The specific conditions of the heat treatment method are: heating to 155 °C at a rate of 2 °C / min under an argon atmosphere and maintaining for 12 h.

[0021] Unless otherwise specified, the materials and reagents used in the present invention can be obtained from commercial products in the art.

[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below according to the accompanying drawings.

[0023] Example 1 A lithium-sulfur battery composite positive electrode material based on sulfur-defective cobalt sulfide composite nitrogen-doped graphene carrier is prepared in the following steps: Step 1, preparation of sulfur-defective cobalt sulfide composite nitrogen-doped graphene; 0.15 g of polyethylene glycol, 0.6 g of cobalt nitrate hexahydrate and 1.5 g of thioacetamide were placed in a mortar and ground for 10 min to mix evenly, then 0.1 g of nitrogen-doped graphene was added and ground for another 20 min. Finally, the uniform mixture was placed in a corundum boat, filled in a tube furnace, calcined at 900 °C for 2 h in a 10% hydrogen / argon atmosphere, and then ground again to obtain cobalt sulfide composite nitrogen-doped graphene containing sulfur defects; Step 2, compounding the cobalt sulfide composite nitrogen-doped graphene containing sulfur defects obtained in step 1 with sulfur; The target carrier material and sulfur were mixed and ground at a mass ratio of 28:72 for 0.5 h, placed in a reactor with an argon atmosphere, and kept at 155 °C for 12 h at a heating rate of 2 °C / min to obtain a lithium-sulfur battery composite positive electrode material (S / Co 9 S 8-x / NG).

[0024] The prepared composite positive electrode material is made into electrode sheets according to the following method, and the battery is assembled and tested: (1) Electrode sheet production The prepared composite cathode material, Super-P conductive agent and polyvinylidene fluoride (PVDF) were selected and ground evenly for 0.5 h in a ratio of 70 wt%, 20 wt% and 10 wt%, and N-methylpyrrolidone (NMP) was added and stirred to a uniform slurry. Then it was coated on a carbon-coated aluminum foil and dried at 60 °C for 12 h to prepare an electrode sheet with a diameter of 10 mm.

[0025] (2) Battery assembly Celgard 2325 was used as the separator and the lithium sheet was used as the negative electrode. The 2032 button cell was assembled in an argon-filled glove box. The assembly sequence was negative electrode shell-spring-gasket-lithium sheet-electrolyte-separator-electrolyte-positive electrode sheet-positive electrode shell. The electrolyte consisted of 1.0 M lithium bistrifluoromethanesulfonyl imide (LiTFSI) and 0.2 M lithium nitrate (LiNO 3 ) additive was dissolved in 1, 2-dimethoxyethane (DME) and 1, 3-dioxolane (DOL) (v / v, 1:1) with an electrolyte to sulfur ratio (E / S) of 12 μL mg -1 The obtained 2032 button cell was placed on the battery testing system, and after standing for 6 h, the charge and discharge test was carried out at a rate of 0.1 C, the voltage cut-off range was set to 1.7-2.8 V, and the composite cathode material was used as the active material. The discharge specific capacity of the battery was calculated, and its initial discharge specific capacity was 1314.6 mAh / g. After 50 cycles, it remained at 998.4 mAh / g, and the capacity retention was 80.6%.

[0026] Example 2 According to the steps in Example 1, a lithium-sulfur battery composite positive electrode material (S / Co 9 S 8-x / NG).

[0027] The obtained composite positive electrode material (S / Co 9 S 8-x / NG) were made into electrodes according to the method in Example 1 and assembled into a battery for testing, wherein the ratio of electrolyte to sulfur (E / S) was 10 μL mg -1 The discharge capacity of the battery was calculated using the composite cathode material as the active material. The initial discharge capacity was 1146 mAh / g, and after 50 cycles it remained at 957.4 mAh / g, with a capacity retention of 82.5%.

[0028] Example 3 According to the steps in Example 1, a lithium-sulfur battery composite positive electrode material (S / Co 9 S 8-x / NG).

[0029] The obtained composite positive electrode material (S / Co 9 S 8-x / NG) were made into electrodes according to the method in Example 1 and assembled into a battery for testing, wherein the ratio of electrolyte to sulfur (E / S) was 8 μL mg -1The discharge capacity of the battery was calculated using the composite cathode material as the active material. The initial discharge capacity was 1137.7 mAh / g, and it remained at 919.5 mAh / g after 50 cycles, with a capacity retention of 78.3%.

[0030] Example 4 According to the steps in Example 1, a lithium-sulfur battery composite positive electrode material (S / Co 9 S 8-x / NG).

[0031] The obtained composite positive electrode material (S / Co 9 S 8-x / NG) were made into electrodes according to the method in Example 1 and assembled into a battery for testing, wherein the ratio of electrolyte to sulfur (E / S) was 6 μL mg -1 The discharge capacity of the battery was calculated using the composite cathode material as the active material. The initial discharge capacity was 1089.5 mAh / g, and it remained at 648.7 mAh / g after 50 cycles, with a capacity retention of 69.1%.

[0032] Compared with other battery tests, the battery assembled with the electrolyte to sulfur ratio (E / S) in the embodiment has a specific capacity and capacity retention rate. The embodiment data are listed in Table 1.

[0033] Table 1 Comparison of battery cycle performance of various embodiments Depend on Figure 2 It can be seen that the discharge curves of the lithium-sulfur battery composite positive electrode materials obtained in Examples 1 to 4 all show two discharge platforms; the first week discharge specific capacities are 1314.6, 1146, 1137.7 and 1089.5 mAh / g, respectively, with a high sulfur utilization rate. And from the above test results, it can be seen that the lithium-sulfur battery composite positive electrode materials with different electrolyte to sulfur ratios (E / S) provided by the present invention all show excellent electrochemical properties. Among them, the composite positive electrode material obtained in Example 1 has the highest initial discharge specific capacity and capacity retention rate, and at a lower electrolyte to sulfur ratio (E / S) of 6 μL mg -1 When the initial discharge capacity and capacity retention rate are high, it also has a high initial discharge capacity and capacity retention rate. This shows that by loading sulfur on cobalt sulfide containing sulfur defects and nitrogen-doped graphene carriers, and utilizing the good charge transfer and strong chemical adsorption of lithium polysulfide by cobalt sulfide containing sulfur defects, a lithium-sulfur battery composite positive electrode material with high sulfur content, high capacity and high cycle stability can be obtained.

[0034] It should be noted that although the present invention is described by the above embodiments, the present invention may also have other various embodiments. Without departing from the spirit and scope of the present invention, it is obvious that those skilled in the art may make various corresponding changes and deformations to the present invention, but these changes and deformations should all fall within the scope of protection of the appended claims of the present invention and their equivalents.

Claims

1. A method for preparing a composite positive electrode material for a lithium-sulfur battery, characterized in that: A one-step sintering method is used to prepare sulfur-defective cobalt sulfide composite nitrogen-doped graphene as a sulfur positive electrode carrier, which is then compounded with sulfur element through a heat treatment method to prepare a composite positive electrode material for lithium-sulfur batteries.

2. The method for preparing a composite positive electrode material for a lithium-sulfur battery according to claim 1, characterized in that: The specific steps include: Step 1: Grinding a cobalt source, a sulfur source, a polymer and nitrogen-doped graphene to obtain a uniform mixture precursor, calcining the mixture precursor under a specific atmosphere, and then grinding it again to obtain a product, namely, sulfur-defective cobalt sulfide composite nitrogen-doped graphene; Step 2: Grind the prepared sulfur-defective cobalt sulfide composite nitrogen-doped graphene and sulfur element continuously for 0.5 h, then place it in a reactor, and heat-treat it to obtain a composite positive electrode material S / Co9S for lithium-sulfur batteries. 8-x / NG.

3. The method for preparing a composite positive electrode material for a lithium-sulfur battery according to claim 2, characterized in that: In step 1, the cobalt source is cobalt nitrate hexahydrate, and the sulfur source is thioacetamide.

4. The method for preparing a composite positive electrode material for a lithium-sulfur battery according to claim 2, characterized in that: In step 1, the polymer is polyethylene glycol with a molecular weight of 20,000.

5. The method for preparing a composite positive electrode material for a lithium-sulfur battery according to claim 2, characterized in that: In step 1, the specific method for preparing the mixture precursor is: firstly place the cobalt source, the sulfur source, and the polymer in a mortar and mix and grind for 9 to 10 minutes, and then add the nitrogen-doped graphene and continue grinding for 19 to 20 minutes.

6. The method for preparing a composite positive electrode material for a lithium-sulfur battery according to claim 2, characterized in that: In step 1, the specific conditions of calcination under the specific atmosphere are calcination at 900° C. for 2 h in a hydrogen / argon mixed atmosphere.

7. The method for preparing a composite positive electrode material for a lithium-sulfur battery according to claim 2, characterized in that: In step 2, the mass ratio of the sulfur-defective cobalt sulfide composite nitrogen-doped graphene to the sulfur element is 28:

72.

8. The method for preparing a composite positive electrode material for a lithium-sulfur battery according to claim 2, characterized in that: In step 2, the specific conditions of the heat treatment method are: heating to 155°C at a rate of 2°C / min under an argon atmosphere and maintaining for 12 h.

9. A composite positive electrode material for a lithium-sulfur battery prepared according to the preparation method according to any one of claims 1 to 8.